Ответ:
Пошаговое объяснение:
5) = 0,6x - 2,2 - 2 + 1,5x = 2,1x - 4,2
6) = 3m - 4n - 5m - 2n = -2m - 6n
7) = -10,5a + 7b + 2,6a - 2b = -7,9a + 5b
8) = -8a + 13 + 12 - 9a = -17a + 25
5) (3x - 11) * 0,2 - 5* (0,4 - 0,3x) = 0,6x - 2,2 - 2 + 1,5x = 2,1x - 4,2
6) 1/6 * (18m -24n) - (5m+2n) = 3m - 4n -5m -2n = -2m - 6n
7) -3,5(3a - 2b) + 2(1,3a - b) = -10,5a + 7b + 2,6a - 2b = -7,9a + 5b
8) -(8a - 13) + 3(4 - 3a) = -8a + 13 + 12 - 9a = -17a + 25
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
5) = 0,6x - 2,2 - 2 + 1,5x = 2,1x - 4,2
6) = 3m - 4n - 5m - 2n = -2m - 6n
7) = -10,5a + 7b + 2,6a - 2b = -7,9a + 5b
8) = -8a + 13 + 12 - 9a = -17a + 25
Ответ:
5) (3x - 11) * 0,2 - 5* (0,4 - 0,3x) = 0,6x - 2,2 - 2 + 1,5x = 2,1x - 4,2
6) 1/6 * (18m -24n) - (5m+2n) = 3m - 4n -5m -2n = -2m - 6n
7) -3,5(3a - 2b) + 2(1,3a - b) = -10,5a + 7b + 2,6a - 2b = -7,9a + 5b
8) -(8a - 13) + 3(4 - 3a) = -8a + 13 + 12 - 9a = -17a + 25